Guidelines for designing an IP survey. (World Intellectual Property Organization, 2022)
Surveys based on intellectual property (IP) can be a valuable tool in designing innovation and IP policies. This short guide outlines best practices for designing IP-related surveys, with the aim of promoting their adoption by governments and researchers keen to understand the economic behavior of stakeholders in the IP system and design policies to assist its development